Integrated marketing communications: a strategic priority in health and medicine - James K. Elrod; John L. Fortenberry (BMC, 2020)
Abstract Background Healthcare establishments portray themselves to their patient populations using many communicative mechanisms. Perhaps the first avenues that come to mind are the outward conveyances of the marketing communications mix, including advertising, personal selling, sales promotion, public relations, and direct marketing. But other prominent communicators also exist, including the people employed by healthcare institutions, the places in which services are delivered, and the brands that represent given establishments. This wide variety of communicative mechanisms is somewhat of a mixed blessing, affording myriad options, but also necessitating extra care and attention in developing associated marketing communications. Discussion Now more than ever, health and medical establishments have at their disposal communications options capable of addressing most any conveyance want or need. The marketing communications mix, once somewhat limited due to industry tradition, is now fully accessible and widely used in the health services industry, providing immense opportunities to connect with patients. Options for signage, building designs, servicescape amenities, employee uniforms, and the like also are teeming, providing myriad avenues for making positive impressions. But burgeoning options while beneficial also intensify obligations for ensuring that marketing communications are properly integrated, with this particular article describing this imperative need and its implications for communicative success in the healthcare industry. Conclusions By integrating marketing communications, health and medical providers are able to create synergies between and among selected conveyance mechanisms, amplifying performance and increasing the likelihood of reaching communicative goals. Achieving such cohesion requires devoted planning in an effort to coordinate verbal and visual manifestations to express desired imagery and appeals to target audiences. As extensive benefits are derived from integrated marketing communications, healthcare establishments should consider associated pursuits to be a strategic priority.